Effectiveness and cost-effectiveness of a health systems intervention for latent tuberculosis infection management (ACT4): a cluster-randomised trial. (May 2021) - Oxlade, Olivia; Benedetti, Andrea; Adjobimey, Mênonli; Alsdurf, Hannah; Anagonou, Severin; Cook, Victoria J; Fisher, Dina; Fox, Greg J; Fregonese, Federica; Hadisoemarto, Panji; Hill, Philip C; Johnston, James; et al.
Summary: Background: Reaching the UN General Assembly High-Level Meeting on Tuberculosis target of providing tuberculosis preventive treatment to at least 30 million people by 2022, including 4 million children under the age of 5 years and 20 million other household contacts, will require major efforts to strengthen health systems. The aim of this study was to evaluate the effectiveness and cost-effectiveness of a health systems intervention to strengthen management for latent tuberculosis infection (LTBI) in household contacts of confirmed tuberculosis cases. Methods: ACT4 was a cluster-randomised, open-label trial involving 24 health facilities in Benin, Canada, Ghana, Indonesia, and Vietnam randomly assigned to either a three-phase intervention (LTBI programme evaluation, local decision making, and strengthening activities) or control (standard LTBI care). Tuberculin and isoniazid were provided to control and intervention sites if not routinely available. Randomisation was stratified by country and restricted to ensure balance of index patients with tuberculosis by arm and country. The primary outcome was the number of household contacts who initiated tuberculosis preventive treatment at each health facility within 4 months of the diagnosis of the index case, recorded in the first or last 6 months of our 20-month study. To ease interpretation, this number was standardised per 100 newly diagnosed index patients with tuberculosis. Analysis was by intention to treat. Masking of staff at the coordinating centre and sites was not possible; however, those analysing data were masked to assignment of intervention or control. An economic analysis of the intervention was done in parallel with the trial. ACT4 is registered at ClinicalTrials.gov, NCT02810678 . Findings: The study was done between Aug 1, 2016, and March 31, 2019. During the first 6 months of the study the crude overall proportion of household contacts initiating tuberculosis preventive treatment out of those eligible at intervention sites was 0·21. After the implementation of programme strengthening activities, the proportion initiating tuberculosis preventive treatment increased to 0·35. Overall, the number of household contacts initiating tuberculosis preventive treatment per 100 index patients with tuberculosis increased between study phases in intervention sites (adjusted rate difference 60, 95% CI 4 to 116), while control sites showed no statistically significant change (−12, −33 to 10). There was a difference in rate differences of 72 (95% CI 10 to 134) contacts per 100 index patients with tuberculosis initiating preventive treatment associated with the intervention. The total cost for the intervention, plus LTBI clinical care per additional contact initiating treatment was estimated to be CA$1348 (range 724 to 9708). Interpretation: A strategy of standardised evaluation, local decision making, and implementation of health systems strengthening activities can provide a mechanism for scale-up of tuberculosis prevention, particularly in low-income and middle-income countries. Funding: Canadian Institutes of Health Research